Catena-poly[[diiodidocadmium] -μ- [4,4′-(2,3,5,6-tetramethyl-1,4- phenylene)bis-(methylene)]bis-(3,5-dimethyl-1H-pyrazole)-κ 2 N 2:N 2′] - Zhou, Yuan Yuan; Wang, Zhao Yang; Yang, Guan; Ng, Seik Weng (International Union of Crystallography, 2011)
The heterocylic ligand of the polymeric title compound, [CdI 2(C 22H 30N 4)], links two adjacent CdI 2 units, forming a chain running parallel to [ 01]. The Cd II atom is located on a twofold rotation axis and shows a distorted tetra-hedral CdI 2N 2 coordination. The mid-point of the benzene ring of the ligand lies on a center of inversion. There are no classical hydrogen-bonding interactions present.